Adomian Decomposition and Successive Approximation Methods for Solving Kaup-Boussinesq System - Manaa, Saad A.; Mosa, Nergiz M. (Science Journal of University of Zakho, 2019)
The Kaup-Boussinesq system has been solved numerically by using two methods, Successive approximation method (SAM) and Adomian decomposition method (ADM). Comparison between the two methods has been made and both can solve this kind of problems, also both methods are accurate and has faster convergence. The comparison showed that the Adomian decomposition method much more accurate than Successive approximation method.